A patient with atrial septal defect with cyanosis with diagnostic dilemma turned out to be a case of Total Anomalous Pulmonary Venous Connection (TAPVC) - Ahsan, Mahbub; Rahman, Md Lutfar; Islam, ASM shariful; Munshi, Prokash Chandra; Rahman, Md Muzibur; Rahman, Md Mezanur (KYAMC Journal, 2021)
Total anomalous pulmonary venous connection (TAPVC) is a congenital cyanotic heart disease where all 4 pulmonary veins do not open directly to left atrium. There are 4 types of TAPVC. Supra cardiac type forms a confluence and may open to Innominate vein or SVC. Cardiac type usually opens to coronary sinus. Infracardiac type opens to hepatic veins or other veins. Mixed type is the combination of others. Of these 4 types infracardiac type is most vulnerable and presents with early features of cyanosis, pulmonary hypertension, pulmonary vein obstruction. We present the case of an 18 year old lady with atrial septal defect (ASD) with cyanosis. Pre operative echo showed ASD with 3rd chamber behind LA, CT angiogram revealed large ASD, with tongue like extended chamber in posteromedial aspect of RA. Preoperative angiogram report was inconclusive. Despite the diagnostic dilemma, we took the challenge and the patient went for open heart surgery. The patient recovered well and discharged on 10 th post operative day. Post operative echocardiogram is encouraging and she is doing fine. KYAMC Journal.2021;12(02): 107-110